Insulin therapy and risk of prostate cancer: a systematic review and meta-analysis of observational studies. - Yan-bo Chen; Qi Chen; Zhong Wang; Juan Zhou (PLoS ONE, 2013)
Background Previous observational studies have shown that insulin therapy may modify the risk of prostate cancer (PCa). However, these studies yielded controversial results. Thus, we performed this meta-analysis to determine whether insulin use was associated with PCa risk in patients with diabetes mellitus (DM). Method A literature search was carried out in PubMed, EMBASE, and Cochrane Library Central database between January 1966 and January 2013. Fixed-effect and random-effect models were used to estimate pooled relative risks (RR) and corresponding 95% confidence intervals (CIs). Subgroup analyses and sensitivity analyses were also performed. Result A total of 11 (10 cohorts, and one case-control) studies published between 2007 and 2013 were included in the meta-analysis, representing data for 205,523 male subjects and 7,053 PCa cases. There were five studies investigating the influence of insulin and other glucose-lowering agents on the risk of PCa , and six studies investigating the influence of glargine and non-glargine insulin. Insulin use was not associated with PCa risk when compared with other glucose-lowering agents (RR=0.89, 95% CI, 0.72-1.09). Use of insulin glargine did not contribute to susceptibility to PCa as compared with use of non-glargine insulin (RR=1.26, 95% CI, 0.86-1.84). Sensitivity analysis confirmed the stability of present results, since no individual study affected the pooled result significantly. Conclusions Our results suggest that, there may be no significant association between insulin use and risk of PCa as compared with other glucose-lowering agents in patients with DM, and there was no substantial evidence for increase risk of PCa among insulin glargine users as compared to non-glargine insulin users. Further studies are warranted to validate these conclusions.